Titel prent: Na de overwinning : de Sigarenmaker (tot de mede-arbeiders): "Dank, kameraden..." - Hahn, Albert
Titel prent: Na de overwinning : de Sigarenmaker (tot de mede-arbeiders): "Dank, kameraden...".